A zone‐plate‐based two‐color spectrometer for indirect X‐ray absorption spectroscopy. (24th May 2019) - Döring, Florian; Risch, Marcel; Rösner, Benedikt; Beye, Martin; Busse, Philipp; Kubiček, Katharina; Glaser, Leif; Miedema, Piter S.; Soltau, Jakob; Raiser, Dirk; Guzenko, Vitaliy A.; Szabadics, Lukas; et al.
Abstract : A new implementation for XAS measurements based on zone plates is presented. With a two‐color scheme, several fluorescence yields can be probed simultaneously. Abstract : X‐ray absorption spectroscopy (XAS) is a powerful element‐specific technique that allows the study of structural and chemical properties of matter. Often an indirect method is used to access the X‐ray absorption (XA). This work demonstrates a new XAS implementation that is based on off‐axis transmission Fresnel zone plates to obtain the XA spectrum of La0.6 Sr0.4 MnO3 by analysis of three emission lines simultaneously at the detector, namely the O 2 p –1 s, Mn 3 s –2 p and Mn 3 d –2 p transitions. This scheme allows the simultaneous measurement of an integrated total fluorescence yield and the partial fluorescence yields (PFY) of the Mn 3 s –2 p and Mn 3 d –2 p transitions when scanning the Mn L ‐edge. In addition to this, the reduction in O fluorescence provides another measure for absorption often referred to as the inverse partial fluorescence yield (IPFY). Among these different methods to measure XA, the Mn 3 s PFY and IPFY deviate the least from the true XA spectra due to the negligible influence of selection rules on the decay channel. Other advantages of this new scheme are the potential to strongly increase the efficiency and throughput compared with similar measurements using conventional gratings and to increase the signal‐to‐noise of the XA spectra as compared with a photodiode. The ability to record undistorted bulk XA spectra at high flux is crucial for future in situ spectroscopy experiments on complex materials.